Brown marmorated stink bug (Hemiptera: Pentatomidae) in Canada: recent establishment, occurrence, and pest status in southern Ontario. Issue 5 (11th March 2014) - Gariepy, T.D.; Fraser, H.; Scott-Dupree, C.D.
Abstract Halyomorpha halys Stål (Hemiptera: Pentatomidae), the brown marmorated stink bug (BMSB), has been intercepted numerous times in Canada, and overwintering BMSB adults have been reported by homeowners. However, established breeding populations were not detected before 2012. Here we report the occurrence of established populations of BMSB in southern Ontario, Canada and describe habitats, host plants, and collection efforts from 2012 to 2013. Tracking the phenology and spread of this pest in Ontario is critical for the development of integrated pest management strategies to prevent severe economic damage due to this pest.